La politique de lutte contre les épidémies carcérales dans les prisons françaises, 1944-1994 - Jean-Lucien Sanchez (Criminocorpus)
From 1944 onwards, the struggle against prison epidemics in French prisons is characterized by the implementation of a health policy aimed at controlling the contagious risk in prison and preventing its spread to the rest of the population. Based on the screening of detainees at the entrance to penitentiary establishments and on the isolation of contaminated persons in health centers, it allows effective control of tuberculosis and syphilis, which are the main contagious diseases that affect prisoners. But it fails in the face of the outbreak of the HIV-AIDS epidemic in the early 1980s. This new epidemic, which takes a dramatic turn with the so-called “contaminated blood affair”, accelerates the decompartmentalization process of prison medicine which in 1994 led to its transfer to the public hospital service.